AT SAMLE ELLER IKKE AT SAMLE - Gilberg, Rolf (Tidsskriftet Antropologi, 2001)
Some people collect because they cannot stop doing so; it is a kind of disease. Other people collect because they have been requested to do so. The pathological collector collects more for the sport of it than for the results. Therefore, the (p) collector will make stringent rules for the sport, so it will not be too easy for newcomers. But collecting is not enough; the collection has to be organized in a proper way. The result of the requested (r) collection depends on the collector’s background and understanding of the matter at hand. The cultural, historic value of a collection can be measured by the amount of information that is added to the objects in the collection. A collection with little or no information on the objects has really low value seen from a cultural, historic point of view. But a p-collector may overlook that fact as long as the objects fulfil the collector’s criteria for making additions to the collection.